Should we Build Mega Transport Project in Cities? The Case of TransPeshawar Pakistan - Sayed Fayaz Ahmad; Sayed Ilyas Ahmad Ilyas Ahmad (Institute of Business Management, 2019)
The research indicates that TransPeshawar Project faces a huge gap for its successful completion and implementation due to many reasons which approve the recommendations of BRT studies conducted worldwide. Its aim is to find out the present status and challenges of mega transport projects carried out in four cities of Pakistan. Total budget, numbers of riders and operating cost were analyzed for each project. It is interesting that all of the three completed projects are not earning enough money to support their own operations. They are still getting a huge amount from the government in order to operate smoothly. In a country like Pakistan, neither had they obtained their objectives nor support the government financially but benefit a specific sect one way or the other way. The situation will be even worse for BRT Peshawar. Therefore it is recommended that the government should prefer roads, highways or motorways instead of such mega projects in cities. The research is focused on a single case study of BRT projects of Pakistan, its findings may apply to such projects in other cities in similar economic and political contexts